2018
DOI: 10.1111/aec.12657
|View full text |Cite
|
Sign up to set email alerts
|

Geographical ecology and conservation of Eugenia L. (Myrtaceae) in the Brazilian Cerrado: Past, present and future

Abstract: Human actions have caused the fragmentation of natural vegetation, habitat loss and climate change. The Cerrado, considered one of the global hotspots of diversity, has suffered great habitat loss due to these factors, which has been aggravated by the agricultural expansion that took place during the last 60 years. In this context, we chose species of the genus Eugenia L. (Myrtaceae) occurring in the Brazilian Cerrado to describe richness patterns and range loss, and determine conservation priorities for the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…Consequences of temperature increase and reduction of the rainfall volume in the most pessimistic scenarios will cause species to change their distribution to transitional regions of biomes with a favourable climate, mainly for non-dormant seeds with a degree of vulnerability. Thus, a greater displacement of the most sensitive species to more humid and milder temperatures in the Cerrado can be expected, as is predicted for certain species (Oliveira et al, 2019b; Velazco et al, 2019). In species of Eugenia , a decrease of richness in Cerrado areas has been verified from the past to the present and tends to continue, in the future, where the species will move towards the south of the Cerrado and other biomes (Oliveira et al, 2019b).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Consequences of temperature increase and reduction of the rainfall volume in the most pessimistic scenarios will cause species to change their distribution to transitional regions of biomes with a favourable climate, mainly for non-dormant seeds with a degree of vulnerability. Thus, a greater displacement of the most sensitive species to more humid and milder temperatures in the Cerrado can be expected, as is predicted for certain species (Oliveira et al, 2019b; Velazco et al, 2019). In species of Eugenia , a decrease of richness in Cerrado areas has been verified from the past to the present and tends to continue, in the future, where the species will move towards the south of the Cerrado and other biomes (Oliveira et al, 2019b).…”
Section: Discussionmentioning
confidence: 61%
“…Thus, a greater displacement of the most sensitive species to more humid and milder temperatures in the Cerrado can be expected, as is predicted for certain species (Oliveira et al, 2019b; Velazco et al, 2019). In species of Eugenia , a decrease of richness in Cerrado areas has been verified from the past to the present and tends to continue, in the future, where the species will move towards the south of the Cerrado and other biomes (Oliveira et al, 2019b). However, changes can be so severe and rapid in populations that there may be a decrease in species richness and extinction at local and regional levels, with greater risk for endemic species (Strassburg et al, 2017).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, these areas were lost in the present, which indicates a range retraction. Indeed, Oliveira et al (2015Oliveira et al ( , 2018 demonstrated that other plants, endemic to "Cerrado", showed a range retraction between LGM and present. As discussed by Ab'Saber (2000) in glacial periods, there was a retraction of "Cerrado" vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results then argue in favor of seed propagation of E. winzerlingii when massive reproduction is required. The contribution in the knowledge of potential uses of Eugenia genus leads us to strengthen the conservation and sustainable preservation of this plant [35].…”
mentioning
confidence: 99%